DAMPAK DESA WISATA SUDAJI TERHADAP PERKEMBANGAN EKONOMI MASYARAKAT DESA SUDAJI KECAMATAN SAWAN KABUPATEN BULELENG - Komang Wistari; Nyoman Danendra Putra; Pradna Lagatama (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2023)
Sudaji Village is one of the popular tourist villages in Buleleng Regency due to its achievements. Despite its popularity and accomplishments, the economic impact generated from its tourism activities has not been very prominent. This research was conducted to examine the economic impact of Sudaji Tourist Village on the local community. This research is a qualitative descriptive study that uses a case study as its approach method. The data sources in this research are observations and interviews as primary data, and document studies as secondary data, which are then processed using interactive data analysis techniques. The results of this research indicate that Sudaji Tourist Village has potential in various fields, including natural, cultural, and human resources potential. The economic impact generated includes direct impacts from tourist expenditures, indirect impacts through local employment, and continuing impacts in the form of expenditures from income derived from tourism activities. Several issues were experienced during the development of Sudaji Tourist Village, including a lack of awareness regarding existing regulations, sectoral ego, insufficient attention from the local government, and a lack of awareness among the local community. To address these issues, several solutions have been implemented, including improving regulations and enhancing the governance system of tourism activitie